(untitled) (Elmergib Journal of Human Sciences, 2026)
This study examines the Quran term Al-Sabians through a syntactic and semantic analysis by tracing its occurrences in the Quran and investigating the variation in its grammatical case between nominative and accusative forms, along with the scholarly debate this variation generated among grammarians and exegetes, the study aims to identify the grammatical foundations underlying this disagreement and to clarify the role of Quran context and variant reading in guiding grammatical interpretation. Adopting an inductive and analytical methodology, the research analyzes the occurrences of the term in Surah Al-Baqarah, Al-Ma’idah, and Al-Hajj, and reviews the views of major grammarians and commentators in relation to contextual meaning. The study concludes that this grammatical variation does not represent a violation of grammatical rules but rather an intentional syntactic choice shaped by Quran context reflects the precision of Quran expression and the flexibility of Arabic grammatical principles.